2021
DOI: 10.3390/s21062212
|View full text |Cite
|
Sign up to set email alerts
|

Smart Assistive Architecture for the Integration of IoT Devices, Robotic Systems, and Multimodal Interfaces in Healthcare Environments

Abstract: This paper presents a new architecture that integrates Internet of Things (IoT) devices, service robots, and users in a smart assistive environment. A new intuitive and multimodal interaction system supporting people with disabilities and bedbound patients is presented. This interaction system allows the user to control service robots and devices inside the room in five different ways: touch control, eye control, gesture control, voice control, and augmented reality control. The interaction system is comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Similar multimodal control frameworks have previously been suggested, but have not been used for continuous control of a robot arm [62]- [64]. These frameworks do not directly combine different modalities to improve control, they instead make multiple modality control options available to the user.…”
Section: B Multimodal Control Interfacesmentioning
confidence: 99%
“…Similar multimodal control frameworks have previously been suggested, but have not been used for continuous control of a robot arm [62]- [64]. These frameworks do not directly combine different modalities to improve control, they instead make multiple modality control options available to the user.…”
Section: B Multimodal Control Interfacesmentioning
confidence: 99%
“…IoT is widely exploited for health-oriented applications [ 2 , 3 , 4 , 5 ], including highly specific solutions, supporting the needs of people with disabilities [ 6 , 7 ], or techniques for non-intrusive, continuous monitoring of relevant physiological parameters (e.g., blood pressure [ 8 ], heart rate [ 9 ]). Wearable sensors are widely used, with the non-wearable approach being sought for further reducing the burden of the user [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Voice-based control, a specific IoT technology application used in healthcare environments, could improve healthcare quality and experience [ 3 5 ]. The voiced-based control system was also an effective way to reduce contamination of surfaces, which could decrease the spread of healthcare-associated infections (HCAIs) with touchless computer interfaces [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since patients are consumers under this condition, studying their points before the voice-based control system's actual implementation is essential. Previous studies conducted in laboratory environments showed that users considered positive with different interaction modes in the wards [ 3 , 6 ]. Here, we conducted an experimental study in the real clinical workflow.…”
Section: Introductionmentioning
confidence: 99%